THE BALTIMORE LONGITUDINAL STUDY ON AGING: 60 YEARS OLD AND BETTER THAN EVER - Ferrucci, L (Innov Aging, 2018)
The Baltimore Longitudinal Study of Aging (BLSA) is among the world‗s longest running longitudinal studies. Started in 1958 by Nathan Shock, the BLSA had been the main source of information on changes in physiology and anatomy that occur with aging, the interface of these changes with emerging disease and trajectories of physical and cognitive decline. In this symposium we will review the history and the challenges to running a study for 60 years and counting, including strategies for maintaining continuity of observation in the face social, medical and technical changes. We will share a sample of BLSA‗s contributions over its legacy, describe the new paradigm for the study of aging implemented during its most recent overhaul and present a newly applied data-sharing plan. After this introduction, three speakers will present scientific projects that exemplify the breadth, depth and innovative data acquired in the BLSA in different domains. Dr. Simonsick will highlight the extensive suite of functional performance assessments from the cellular to whole body level providing examples from recent publications and ongoing analyses. Dr. Chiles Shaffer addresses the study of racial disparities. In BLSA black participants have similar socio-economic status as white participants but racial differences in health and physical performance are still observed. Dr. Tian will present the comprehensive assessment of brain function including extensive cognitive performance testing and brain imaging studies including functional MRI and PET studies and highlighting the integrative work connecting gait and brain function.